2017
DOI: 10.1007/s40430-017-0729-5
|View full text |Cite
|
Sign up to set email alerts
|

Coupled radiative-conductive heat transfer problems in complex geometries using embedded boundary method

Abstract: List of symbols A Surface area [m 2 ] G Incident radiation [W/m 2 ] I Radiative intensity [W/m 2 sr] k Thermal conductivity [W/m K] L Length [m] M Number of discrete directions n Unit vector perpendicular to the surface N cr Conduction-radiation parameter (=kβ/4σT 3) q Thermal flux [W/m 2 ] r Position vector [m] S Source term [W/m 3 ] T Temperature [K] V Volume [m 3 ] w Quadrature weight x, y, z Coordinate [m] D m ci Directional weight f i Area fraction of embedded control surface F ij Volume fraction of embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…To present the results of the LBM-LBM algorithm and ensure its accuracy, two different geometries are considered, as shown in Figure 7. These figures are usually used as the benchmark to check the performance and validity of results and analyze the outcomes (Amiri et al , 2010; Sun and Zhang, 2018; Zabihi et al , 2017; Bouzgarrou et al , 2017; Zhou et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…To present the results of the LBM-LBM algorithm and ensure its accuracy, two different geometries are considered, as shown in Figure 7. These figures are usually used as the benchmark to check the performance and validity of results and analyze the outcomes (Amiri et al , 2010; Sun and Zhang, 2018; Zabihi et al , 2017; Bouzgarrou et al , 2017; Zhou et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…[16] When the blocked-off method is combined with the discrete ordinates method (DOM) or the finite volume method (FVM) to solve the radiative trans-fer equation (RTE), the complex walls are actually approximated as stair-like boundaries, which brings difficulties in determining the radiative heat flux at the irregular boundaries. Many researches have shown that the obtained radiative heat flux from the blocked-off method is highly oscillating [17,26] as shown in Fig. 1(a).…”
Section: Introductionmentioning
confidence: 99%
“…There are some modifications to this issue, but the outcome is not very satisfactory. [26][27][28][29][30][31] Young Byun et al [17] showed that the multiblock, blocked-off and embedded boundary method can be used to calculate the radiative heat flux on regular walls accurately, while on the irregular wall, the blocked-off method has poor accuracy. Zabihi et al [26] compared the blocked-off method with embedded boundary method for radiative heat flux along the inclined boundary and curved boundary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation